The Social Conflict in Que Nguyen and Adele Lim's Raya and The Last Dragon - Sabatini, Yosica Gabrellia; Andayani, Ambar (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research is entitled The Social Conflict in Que Nguyen and Adele Lim’s Raya and the Last Dragon. The focus of this research is divided into two, namely to analyze the social conflict and conflict resolution within the story. The primary data source is the screenplay of Raya and The Last Dragon by Que Nguyen and Adele Lim. This study uses sociological approach which focuses on Marxist literary criticism to analyze the social conflict between the bourgeoisie and the proletariat, as well as how the conflict resolution unfolds. This study employs a descriptive qualitative method. The results show that social conflict is reflected through class structure in an unequal economic system in the form of the bourgeoisie and the proletariat, as well as class conflict in the form of inequality of power resources, class resistance, and struggle for power resources. Moreover, conflict resolution is depicted in the form of class consciousness, working class unity, and social change. Thus, the study concludes that social conflicts rooted in class inequality can lead to divisions, betrayals, and struggles for power resources among groups who are suspicious of each other, and this story emphasizes that consciousness of injustice, unity among the oppressed, and collective action between them are important keys to achieve justice, equality, and sustainable peace. Keywords: bourgeoisie, class structure, conflict resolution, proletariat, social conflict,